MODEL ENTREPRENEURSHIP EDUCATION TOURISM BATIK IN INDONESIA - Eny Kustiyah; Siti Nurlaela; Amir Junaidi; Bambang Mursito (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research is to support the conditional aspect of entrepreneurial networks, the development of sustainable tourism destinations provides an opportunity for government parties to jointly commit themselves in the role of developing balanced, harmonious and targeted objectives to realize sustainable tourism objectives, including in this case tourism education Batik in addition, in order to respond to changes in current tourism trends in which the awareness of tourists about environmental issues is higher. Batik tourism is a sustainable tourism development in order to stay competitive with other countries. Key Word: Entrepreneur Network, tourism Education of Batik